Incidencia del programa vamos con todo del canal RTS, en la formación social de los habitantes del barrio Cuba - Bustos Bohórquez, Miriam Elena (2016)
This paper aims to show the reality that is part of daily life, analyzing the content and form of generating rating of this program specifically showbiz. A work of great importance as through surveys, investigations, testimonies and reports, analyzing the content of the program was conducted showbiz……